Association between external ophthalmoplegia with diplopia due to brain injury and FIM motor items: a case-control study - Suzuki, Hisayoshi; Abe, Marina; Kawate, Nobuyuki; Yoda, Mitsumasa; Watabe, Takayuki; Sako, Rikitaro (Japanese Journal of Comprehensive Rehabilitation Science, 2022)
Watabe T, Abe M, Sako R, Suzuki H, Yoda M, Kawate N. Association between external ophthalmoplegia with diplopia due to brain injury and FIM motor items: a case-control study. Jpn J Compr Rehabil Sci 2021; 12: 58‒63.Objectives: This study aimed to determine the association between the presence of external ophthalmoplegia with diplopia due to brain injury and Functional Independence Measure (FIM) motor items in a case-control study.Methods: The subjects were patients with brain injury, admitted to a convalescent rehabilitation ward, who were able to walk under supervision and had preserved intellectual function. The correlation between the strabismus angle of the external ophthalmoplegia group and the total points of FIM motor items were examined. In addition, the total points and sub-items were compared between the external ophthalmoplegia group and control group using statistical processing.Results: There were 78 subjects: 34 in the external ophthalmoplegia group and 44 in the control group. Strabismus angle and the total points of FIM motor items of the external ophthalmoplegia group were significantly negatively correlated. Compared with the control group, the external ophthalmoplegia group had significantly lower levels of independence in bathing, dressing (lower body), toileting, transfer to the chair, transfer to the toilet, transfer to the bathroom, and locomotion (walking).Conclusions: External ophthalmoplegia with diplopia is associated with FIM motor items.